Analisis Sintaksis Klausa Bebas dalam Teks Percakapan Para Pengguna Facebook Berdasarkan Pola Bahasa Indonesia Sehari-hari di Media Sosial (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study aims to examine in-depth the forms and types of clauses that appear in everyday conversations on social media, particularly on the Facebook platform. The focus of the study is directed at how social media users form and use clauses in online interactions, and their implications for message comprehension. This study uses a qualitative descriptive method with data collection techniques consisting of observations of conversations and interactions between users. The collected data are then analyzed to identify patterns, variations, and characteristics of the clauses used. The results show that the language forms used tend to be non-standard, for example, short sentences, omissions of subject or predicate elements, and the use of informal vocabulary. However, these variations do not hinder the understanding of messages between users. Instead, the use of these forms reflects users' adaptation to the nature of online communication, which demands speed and efficiency. This phenomenon demonstrates the flexibility of language that is constantly evolving in response to changes in social and technological contexts. The research findings confirm that language dynamics in the digital era not only influence clause form and structure but also enrich the variety of contemporary Indonesian discourse. This has important implications for education, particularly in language learning. By understanding the role of clauses in online communication, educators can adapt teaching methods to be more relevant to the linguistic realities faced by students. This research contributes to the study of sociolinguistics and digital communication, while also opening up opportunities for further research. Future, more in-depth studies could explore the influence of online interactions on language development, the relationship between language and culture, and how technology shapes communication patterns in society.